The effect of food safety compliance on emerging farmers and sustainable farming in the Western and Eastern Cape provinces of South Africa - Terblanche, S.E. (Stephanus Esaias), 1940- (University of Pretoria, 2020)
Dissertation (MSc (Agric))--University of Pretoria, 2019.